The Influence of The Family Environment and Grit on Student's Academic Self-Efficacy - Nurul Zalfa Putri Winandari; Najlatun Naqiyah (Bisma The Journal of Counseling, 2022)
The Covid-19 pandemic has caused students to no longer be able to carry out face-to-face meetings as usual, this has hampered their personal and social development. This study will focus on seeing whether there is an influence between the family environment and grit on academic self-efficacy. Using simple random sampling technique, this study involved 106 7th and 8th grade students of SMPN Surabaya, Indonesia. The instruments used in this study were parenting style questionnaires, persistence questionnaires and academic self-efficacy questionnaires. The results showed that the F test was 12,361 and the significance was 0.000 > 0.05 indicating that there was a significant effect between family environment and grit on the academic self-efficacy of junior high school students. So that a good family environment in this case parenting will affect the child's self-efficacy, in this study authoritarian parenting is the parenting pattern that has the most positive influence on self-efficacy. Then to improve academic self-efficacy, parents and teachers must collaborate to create a family and school environment that supports children to develop well.